Contradicting perceptions of nursing teachers on the neoliberal context of labor - Camila Arantes Ferreira Brecht D’ Oliveira; Márcia Tereza Luz Lisboa; Carolina Cabral Pereira da Costa; Sheila Nascimento Pereira de Farias; Thereza Christina Mó y Mó Loureiro Varella; Ellen Marcia Peres; Norma Valéria Dantas de Oliveira Souza (Revista Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: To identify and analyze the perceptions of nursing teachers on the new configurations of the job world and the repercussions for their labor activities. Methods: Qualitative, descriptive, exploratory research, carried out at two federal nursing colleges in Rio de Janeiro. Data collection occurred with 27 nursing teachers, between May and June 2016, through semi-structured interviews. The data were treated using the thematic content analysis technique. Results: The results showed contradictions in the teachers’ perceptions about the job world, which has been guided by neoliberal precepts. Such contradictions are characterized by manifestations in favor of incorporating these precepts, highlighting their negative effects on nursing teaching work. Final considerations: There are incongruities in the way of perceiving the current configuration of the job world, proposing more and profound reflections on such a work scenario.